Information platform to improve technological innovation capabilities: role of cloud platform - Yang, Li-Ren; Huang, Chung-Fah (Journal of Civil Engineering and Management, 2016)
Conceptualizing technological innovation capabilities and cloud platform implementation in the construction management context is still rudimentary. The primary objective of this study was to validate a model for assessing the relationships among information platform usage, technological innovation capabilities, and capital facility project performance. This study also evaluated the moderating role of type of platform in the relationships. This study empirically investigated a sample of projects in the Taiwanese construction industry. The structural equation modeling (SEM) approach was used to validate the research model. In testing the moderation effect, two-way analysis of variance (ANOVA) was used. The findings indicate that implementation of information platform contrubutes significantly to technological innovation capabilities. In addition, these analyses suggest that technological innovation capabilities have a positive effect on project performance. The results also show that the relationship between information platform usage and technological innovation capabilities depends on type of platform (i.e., traditional or cloud-based information management platform). This indicates that the association between technological innovation capabilities and project performance is more strongly evident for projects that use cloud platform.